Comparison of methods to assess airborne rat and mouse allergen levels. I. Analysis of air samples. - Hollander, A; Gordon, S; Renström, A; Thissen, J; Doekes, G; Larsson, P; Malmberg, P; Venables, K; Heederik, D (1999)
Airborne laboratory-animal allergens can be measured by several methods, but little is known about the effects of important differences in methodology. Therefore, methods used in research projects in The Netherlands, the UK, and Sweden were compared. Seventy-four sets of three parallel inhalable dust samples were taken by a single operator in animal facilities in the three countries, and analyzed in parallel by the three institutes for rat and mouse urinary allergen. Rat-allergen levels measured by RAST inhibition (UK) were 3000 and 1700 times higher than levels measured by enzyme immunoassay (EIA)-sandwich methods with polyclonal rabbit (The Netherlands) or monoclonal mouse (Sweden) antibodies, while the difference between the two EIA-sandwich methods was much smaller: a factor of 2.2. For mouse allergen, an inhibition radioimmunoassay (RIA) with rabbit antimouse antibodies (UK) gave 4.6 and 5.9 times higher concentrations than sandwich EIAs with rabbit polyclonal antibodies (Sweden and The Netherlands), while the difference between the two sandwich EIAs was, on average, 1.6-fold. Thus, although levels of rat and mouse aeroallergens are significantly correlated, the assay type gives large differences in absolute concentrations, and interlaboratory technical differences affect even the same assay type. Conversion factors can aid comparison between studies, and, in the long term, assay standardization is desirable.